Resident Supervision and Patient Care: A Comparative Time Study in a Community‐Academic Versus a Community Emergency Department. Issue 4 (24th April 2019) - Wang, Ernest E.; Yin, Yue; Gurvich, Itai; Kharasch, Morris S.; Rice, Clifford; Novack, Jared; Babcock, Christine; Ahn, James; Bowman, Steven H.; Van Mieghem, Jan A.
Abstract: Objective: The objective was to compare attending emergency physician (EP) time spent on direct and indirect patient care activities in emergency departments (EDs) with and without emergency medicine (EM) residents. Methods: We performed an observational, time–motion study on 25 EPs who worked in a community‐academic ED and a nonacademic community ED. Two observations of each EP were performed at each site. Average time spent per 240‐minute observation on main‐category activities are illustrated in percentages. We report descriptive statistics (median and interquartile ranges) for the number of minutes EPs spent per subcategory activity, in total and per patient. We performed a Wilcoxon two‐sample test to assess differences between time spent across two EDs. Results: The 25 observed EPs executed 34, 358 tasks in the two EDs. At the community‐academic ED, EPs spent 14.2% of their time supervising EM residents. Supervision activities included data presentation, medical decision making, and treatment. The time spent on supervision was offset by a decrease in time spent by EPs on indirect patient care (specifically communication and electronic health record work) at the community academic ED compared to the nonacademic community ED. There was no statistical difference with respect to direct patient care time expenditure between the two EDs. There was a nonstatistically significant difference in attending patient load between sites. Conclusions: EPs in our study spent 14.2% of their time (8.5 minutes/hour) supervising residents. The time spent supervising residents was largely offset by time savings related to indirect patient care activities rather than compromising direct patient care.